Evaluation of solar tunnel dryer for green leaves drying - Sengar, S H; Burbade, R G; Divyesh, Vaghela; Abhishek, Parmar (Journal of Postharvest Technology, 2018)
Solar tunnel dryer having 30 m2area was fabricated, developed and evaluated at Department of Renewable Energy Engineering, CAET, Dediapada. The performance of solar tunnel dryer was tested at no load and with load condition. Maximum average temperature was observed during no load test in solar tunnel dryer was 45.6 °C and solar intensity was 496 W/m2 at 1 p.m. as ambient temperature was 28.3 °C, with relative humidity 70 percent. Maximum average temperature was observed during load test of all selected green leaves drying was 46.6 °C and solar intensity was 496 W/m2at 1 p.m. as ambient temperature was 28.5 °C , average humidity 45 % and average wind speed observed as 1.1 m/s. Initial moisture content of Sargava, Neem, Heena and Tulsi leaves were observed as 69.6 %, 74.67 %, 62.8% and 71.30 % respectively. Time required to remove moisture up to storage moisture content as below 10 % from Sargava, Neem, Heena and Tulsi leaves as 8 hours, 6 hours, 8 hours and 8 hours respectively. In open condition time required to remove moisture content up to 26.8 % from Sargava leaves was 8 hours whereas in same time only 46.9 % moisture removed from Heena leaves.